Design of three phase induction motor using MATLAB with application of GUI / Mohd Faiz Shamsuddin - Shamsuddin, Mohd Faiz (2010)
This project presents the method of designing three phase induction motor using MATLAB software, where the main objective is to obtain stator and rotor design, and calculate the circuit parameters base on motor specification. The function of MATLAB programming is to provide an interactive and integrated environment that allows performing mathematical computations, generating plot, writing programs and creating Graphical User Interface (GUI) [1]. The program was developed using MATLAB & GUI programming. From this project, value of induction motor parameters can be obtained easily by using this program.